Dengue in Pregnancy (Bangladesh Journal of Obstetrics & Gynaecology, 2019)
Dengue fever during pregnancy is increasing day by day in Bangladesh. The knowledge of adverse effects on mother and neonate remains limited and there are also lack of management guideline in this regard. Mortality rate for severe dengue fever is 0.8–2.5%, and pregnancy should be considered as a coexisting risk factor for serious infection. However, the maternal and fetal outcomes not fully understood. Some review articles on outcomes of neonates born to mother with dengue fever was reported, and demonstrated that preterm birth and low birth weight were the most common adverse pregnancy outcomes; however, dengue fever was not significantly associated with these adverse outcomes, suggesting that symptomatic dengue fever may indicate risk. Other adverse effects such as stillbirth or postpartum hemorrhage (PPH) remain unclear. Therefore, we aimed to brief review of recent management guideline of OGSB about dengue fever in pregnancy.Bangladesh J Obstet Gynaecol, 2019; Vol. 34(1): 36-42